PHYSICAL PROPERTIES OF CHINESE HERRING (Hilsentoli sp.) LEATHER TANNED WITH CHROME AND RETAINED WITH SYNTHETIC AGENT - Suryaningrum, Th. Dwi; Nuridha, Ahmad; Sinurat, Ellya; Basmal, Jamal; Ariyani, Farida; Utomo, Bagus Sediadi Bandol; Kusumawati, Rinta; Prodiana, Natalia; Supriyanto, Agus; Mardiyana, Indri; Ikasari, Diah (:Agency for Marine and Fisheries Research and Human Resources, Indonesia, 2025)
When the scales of Chinese herring (Hilsentoli sp.), like those of snakes or monitorlizards, are tanned, they exhibit a unique scaly texture with an attractive natural pattern. This study aimed to evaluate the physical properties of Chinese herring skin tanned with chrome and retained with a synthetic agent. The treatments consisted of a combination of chrome and tanning agents at various concentrations, ie. Chrome (C) 6% and tanning agent (S) 0% (C6S0), Chrome 8% and tanning agent 0% (C8S0), Chrome 10% and tanning agent 0% (C10S0), Chrome 6% and tanning agent 4% (C6S4), Chrome 8% and tanning agent 4% (C8S4), Chrome 10% and tanning agent 4% (C10S4), Chrome 6% and S 6% (C6S6), Chrome 8% and S 6% (C8S6), and Chrome 10% and tanning agent 6% (C10S6). Observations were conducted based on descriptive sensory, physical, and chemical tests, identification of functional groups of the leather, and morphology analysis of the skin leather. The results showed that a combination of chrome and synthetic tanning produced leather with a denser and fuller texture than leather tanned with the chrome tanning agent. C10S6 treatment produced the best physical properties of tanned skin of Chinese herring in terms of its high tensile strength, tear strength, stitch strength, and shrinkage temperature, along with the lowest elongation. The values are well within the Indonesian standard of SNI 0253:2009 for leather with fancy motifs on finished leather goods. The analysis of the cross-section of skin at various treatments using Scanning Electron Microscope (SEM) analysis indicates that retanning with synthetic tanning agents strengthened the collagen matrix, producing denser, more compact structures. This density is caused by the presence of collagen compound bonds and synthetic tanning materials, such as phenol and formaldehyde, which were detected as 2,4-dimethyl phenol in the Raman spectra shift at 208, 35 – 2445.87 cm -1 .